TOTAL WAR IMPLEMENTED IN DEFENCE DIPLOMACY: CASE STUDY OF THE RE-NEGOTIATION OF THE DEFENCE COOPERATION AGREEMENT BETWEEN THE GOVERNMENT OF THE REPUBLIC OF INDONESIA AND THE GOVERNMENT OF THE REPUBLIC OF SINGAPORE (DCA INDONESIA-SINGAPORE) - Syarifuddin, Kurniawan Firmuzi; Prakoso, Lukman Yudho; Widjayanto, Joni (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2021)
Total war is not always associated with power seizure using physical means, however, the real meaning is how a country could implement the whole of resources to fight for their national interest. This study is aimed to provide an understanding that total war could be implemented in all areas of activities. The study is conducted with a qualitative descriptive method through a case study approach, library study, interview, and observation in the field. It has been implemented in defense diplomacy accordingly without our awareness. For instance, in the case of the delay in the Indonesia-Singapore Defence Cooperation Agreement (DCA) renegotiation which unites all personnel from different agencies and institutions, as well as all professional fields to come up with the same directions for Indonesia national interest. This study concludes that a total war strategy could be implemented in defense diplomacy to get a maximum result to fight for Indonesia’s national interest.